SYNTHESIS OF ECOENZYMES FROM ORANGE AND PINEAPPLE PEEL WASTE WITH VARIABLE FERMENTATION TIME TO YIELD AS ORGANIC FERTILIZER - Winarni; Athiek Sri Redjeki; Tri Yuni Hendrawati (Journal of Applied Sciences and Advanced Technology, 2025)
Most of the waste currently available is organic waste originating from household activities in the form of food scraps, seed shells from fruit and vegetables, and fruit waste. The accumulation of organic waste triggers natural decomposition, releasing methane (CH4) gas. This gas not only contributes to increased greenhouse gas levels in the atmosphere, but its accumulation under landfills also has the potential to cause explosions. Organic waste from fruit and vegetables can be processed into ecoenzymes through a fermentation process. Ecoenzymes have many uses, including fertilizer, pest control, antiseptic soap, and household cleaners. The purpose of this research was to determine the effect of time. The resulting ecoenzymes will be used as organic fertilizer. A quantity of orange peel and pineapple peel of 150 grams, respectively, was added to 100 grams of finely ground palm sugar and 1000 ml of water, then fermented for 0, 7, 14, 21, 28, 35, 42, 49, and 56 days. The fermentation results were then measured for pH and organoleptic tests were carried out in the form of visual color and aroma and tested for nitrogen (N), diphosphorus pentoxide (P2Os) and dipotassium oxide (K2O) content. The ecoenzyme obtained was then added with ash to increase the levels of N, P2O5, K2O. Based on the research results, the best time was 56 days and the best raw material ratio was 1:3:10 producing an ecoenzyme that was cloudy brown in color and had a sour aroma and a pH of 3.11. The total N, P2O5, and K2O content of the ecoenzyme produced from the fermentation process was 0.13%. The liquid organic fertilizer produced from the ecoenzyme with the addition of ash had a pH of 6,3. After adding ash, the N, P2O5, K2O content increased to 1.6%. This result still does not meet the standards of the Minister of Agriculture of the Republic of Indonesia which requires a minimum N, P2O5, and K2O content of 2%.